(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
This paper will analyze how and to what extent terrorists and violent extremists have interacted with generative artificial intelligence so far and identify potential ways in which they could misuse generative AI in the future. It is therefore necessary to question assumptions that terrorist and violent extremist actors will quickly adopt generative AI solely based on an assessment of the capabilities it may offer. Although research has shown that technological capability and availability are key drivers of terrorist innovation, terrorist and violent extremist actors also assess any new technology on its compatibility (with both their modus operandi and ideology), relative complexity, cost, and the context in which they are operating. Understanding these factors, both in isolation and in relation to one another, will be a key aspect in monitoring the extent to which terrorists and violent extremists adopt generative AI tools. In doing so, the paper will seek to identify a likely trajectory for the abuse of this technology by terrorist actors as well as conclude with some initial recommendations for policymakers.